Development And Initial Implementation Of EPRI's Coal Quality Impact Model (CQIM) In The Southern Electric System - C. N. Logan (Society for Mining, Metallurgy & Exploration, 1990)
The Southern Company is one of the nation's largest electric utilities and is the parent firm of five operating companies: Alabama Power, Georgia Power, Gulf Power, Mississippi Power and Savannah Electric and Power. Another subsidiary is Southern Company Services (SCS) which provides engineering and technical sup-port to the five operating companies. This technical support includes the procurement and supply of over 40.9 Mt (45 million st) of coal annually for the 22 coal fired plants in the system. Approximately 80 percent of this tonnage is purchased under long term contracts and the remaining 20 percent is purchased on the spot market. The coal is principally supplied from Alabama, Illinois Basin and the eastern Appalachian coal fields. Most of the coal is delivered by unit train and barge but one plant in Alabama receives all its coal by truck and conveyor belt.